CD56 Expression in Odontogenic Cysts and Tumors - Zohreh Jaafari-Ashkavandi; Ali Dehghani-Nazhvani; Faranak Razmjouyi (Tabriz University of Medical Sciences, 2014)
Background and aims. Odontogenic cysts and tumors have a wide spectrum of clinical characteristics that lead to the different management strategies. Since definite diagnosis is difficult in some cases, it has been suggested that CD56 may be a candidate marker for definitive diagnosis of some odontogenic tumors. The present study was designed to examine CD56 expression in lesions with histopathological similarities. Materials and methods. In this cross-sectional, analytical study the subjects were 22 ameloblastomas, 13 dentigerous cysts, 10 keratocystic odontogenic tumors (KCOT), 4 adenomatoid odontogenic tumors (AOT), 3 orthokeratinized odontogenic cysts, 3 calcifying odontogenic cysts (COC) and one glandular odontogenic cyst (GOC). All the samples were examined for CD56 immunoreactivity. Data were analyzed using chi-square test. Results. Twenty cases (91%) of ameloblastomas, 3 (75%) AOT, 4 (40%) KCOT and one case of GOC were positive for CD56. None of the dentigerous cysts, COC and orthokeratinized odontogenic cysts was CD56-positive. There was a significant difference in the CD56 expression between ameloblastoma and dentigerous cyst, as well as COC. Also, KCOT showed significantly higher expression than orthokeratinized odontogenic cyst. Conclusion. In this study CD56 expression was limited to the odontogenic tumors and more aggressive cystic lesions. This marker can be a useful aid for distinguishing cysts and tumors from similar lesions.